De verbo causativo a marcador discursivo em Santa Catarina - Scherer, Eliane (2014)
This study focused the linguistic change of the causative verb deixar (let) followed by verbs of perception or cognition like ver (see), pensar (think) and lembrar (remember) according to a Funcionalist approach. The objective was to describe and analyze the use of let in the imperative form + pronoun (tonic or atonic) or Ø + perception or cognition verb (imperative (+participle)), as in let me (I) see, let me (I) think and let me (I) remember in different cities in the state of Santa Catarina (SC). The study also considered the deletion of the pronoun as let see or the shortening form of the item. The linguistic forms analyzed were considered in their use as a Discourse Marker, used in order to plan the speech mentally and maintain the turn of speech. The data of 12 informers was collected from the project called “Variação e Mudança no Português do Oeste de Santa Catarina” financed by Chamada Pública FAPESC nº 04/2012 Universal, coordinated by the professor Cláudia Rost Snichelotto with syncronic samples done in Chapecó, stratified in sex/gender, age, schooling, monolingual in Portuguese and also by the synchronic samples of the data bank VARSUL with 96 informers done in SC in the nineties, which contemplates the same cells (sex/gender, age, schooling) in four cities of SC: Chapecó, Blumenau, Lages e Florianópolis. Thus, this dissertation recognized that social and stylistic factors could be determinant for the linguistic choices, considering that each speaker, depending on the communicative situation, could produce different uses of the items analyzed. Besides, emergent grammar was considered through the use of language, and, in this way, it was possible to delimitate the context of production in which the item occured, as well as the different forms that were recurrent. So, the frequency of the item was also important to define a possible process of grammaticalization to the phenomena in analysis. This study had financial support from “Chamada Pública FAPESC nº 02/2013”.